ECTOPIC PREGNANCY AT 17 WEEKS: A CASE REPORT - Zakia Zaman; Samreen Fakeer Muhammad; Rozina Khatoon; Hira Fatima (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Ectopic pregnancy remains a substantial cause of maternal morbidity and mortality, especially when it is diagnosed and managed at the advanced gestational age of 17 weeks. A 28-year-old woman presented to the emergency department with acute abdominal pain and signs of hypovolemic shock at 17 weeks’ gestation. Physical examination revealed cervical excitation, adnexal tenderness, and hemoperitoneum on bedside imaging, which was consistent with the findings of ectopic pregnancy. The patient underwent emergency laparotomy, during which the ruptured ectopic pregnancy in the distal part of the right fallopian tube was identified, leading to the right salpingectomy. The patient had an uneventful recovery postoperatively. This case indicates that a high index of suspicion for ectopic pregnancy should be considered even at an advanced gestational age and that it is crucial to identify and intervene promptly to prevent unfavorable consequences. Future studies should focus on improving diagnostic algorithms, surgical techniques, and experience, as well as postoperative treatment to improve outcomes in this clinical setting.